1994
DOI: 10.1136/thx.49.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentration of 7S collagen and prognosis in patients with the adult respiratory distress syndrome.

Abstract: Background -7S collagen, an N-terminal peptide of type IV collagen, is a primary constituent of the basement membrane. To evaluate whether the serum concentration of 7S collagen reflects the severity of inflammatory lung disease, the serum concentration of 7S collagen was measured in patients with adult respiratory distress syndrome (ARDS) and idiopathic pulmonary fibrosis (IPF). Methods -A radioimmunoassay was used for the measurement of 7S collagen. Gas exchange abnormality was expressed as the arterial oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 8 publications
3
22
0
Order By: Relevance
“…1) and bronchoalveolar lavage (BAL) TNF-α, IL-1β, IL-2, IL-4, IL-6 and IL-8 levels than survivors [49,50]. Although cytokine levels may not reflect activity, these findings are similar to those reported by others (table 4) and agree with studies indicating that the evolution of ARDS is determined by the extent of initial pulmonary HDR in the form of alveolar denudation, basement membrane destruction, vascular permeability and quantity of intra-alveolar exudate [74][75][76][77].…”
Section: The Host Defence Response In Ardssupporting
confidence: 82%
“…1) and bronchoalveolar lavage (BAL) TNF-α, IL-1β, IL-2, IL-4, IL-6 and IL-8 levels than survivors [49,50]. Although cytokine levels may not reflect activity, these findings are similar to those reported by others (table 4) and agree with studies indicating that the evolution of ARDS is determined by the extent of initial pulmonary HDR in the form of alveolar denudation, basement membrane destruction, vascular permeability and quantity of intra-alveolar exudate [74][75][76][77].…”
Section: The Host Defence Response In Ardssupporting
confidence: 82%
“…Among these, type IV collagen is the major component of the basement membrane. Both epithelial and endothelial basement membrane destruction are important in the pathogenesis of idiopathic pulmonary fibrosis (IPF) [24] or ARDS [25]. Thus, the present study focused on the type IV collagenolytic MMPs such as MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Although the progression of neutrophil-mediated lung injury is very complex, it is evident that the destruction of the endothelial basement membrane has a central role. 13,14 The basement membrane of the capillary endothelium and the alveolar epithelium is a complex of type IV collagen. MMPs and serine proteases are the primary neutrophil products that can target the basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…12 MMPs released from activated neutrophils degrade type IV collagen, which provides the framework for the basement membrane of pulmonary capillaries, and interstitial collagen and proteoglycan. 13,14 Aside from direct collagenolysis, MMPs inactivate endogenous antiproteases, allowing unrestricted protease activity. 15 Studies by Golub et al have confirmed that, by nonantimicrobial mechanisms, chemically modified tetracyclines (CMTs) can directly inhibit MMPs and prevent activation of pro-MMPs to MMPs by scavenging reactive oxygen species.…”
Section: See P 333mentioning
confidence: 99%